Cancer patients' experience of oncology services in Assam, India. (March 2021) - Oswal, Kunal; Kanodia, Rishav; Nadkar, Umakant; Kharodia, Neha; Avhad, Mahendra; Venkataramanan, Ramachandran; Sethuraman, Lakshman; Caduff, Carlo; Purushotham, Arnie
Highlights: The paper provides an insight into critical areas focusing on diagnosis, treatment, continuum of care and communication during cancer patients' care in India. Healthcare policy needs to focus on developing a robust, holistic, healthcare system. The focus must be in terms of accessibility, affordability and psychosocial care, including counselling and financial support, to ensure better cancer outcomes. Abstract: Background: Cancer patients' experience is dependent on the complex interaction between the patient, carer, healthcare practitioners and healthcare system. The aim of the study was to assess the experience of cancer patients in Assam in order to identify potential areas for improvement in delivering high quality cancer care. Methods: A cross sectional patient experience survey was conducted in 400 patients using structured interviews and pre-tested questionnaires that collected patient-reported outcomes including access to cancer care, experience while availing cancer services across the pathway, waiting times, communication and counselling support, out-of-pocket expenditure and advice regarding available insurance schemes and financial support. Results: The cancer patient's experience of accessing healthcare in Assam is variable with principal challenges being financial constraint and geographical distance to healthcare facilities. Overall, patients' experience during registration, first consultation, pre-treatment and during treatment was good with high satisfaction rates expressed in several of the areas assessed. Areas that were identified for improvement were better explanation of long-term side effects of treatment, enhanced guidance in choosing treatment options and greater support from healthcare professionals to help patients cope with the psychological, emotional and physical aspects of their cancer diagnosis, treatment and recovery. Conclusion: Understanding cancer patient experiences across their journey is critical to delivering accessible and affordable care. Effective, adaptive and responsive communication remains the anchor of excellent patient-centred care especially in resource constraint settings. Policy statement: The paper provides an insight into critical areas focusing on diagnosis, treatment, continuum of care and communication during cancer patients' care in India. Healthcare policy needs to focus on developing a robust, holistic, healthcare system in terms of accessibility, affordability and psychosocial care, including counselling and financial support, to ensure better cancer outcomes.